29 Mart 2006 Tam Güneş Tutulması ve Amatör Gözlemleri - Özışık, Tuncay (İstanbul Kültür Üniversitesi Yayınları, 2005)
Ülkemiz 11 ağustos 1999 tarihinde şahit olduğu Tam güneş tutulmasından sonra 29 Mart 2006 tarihinde tekrar bir tam güneş tutulması yaşayacaktır. Bu tutulma uygun meteorolojik koşullar olduğu takdirde Batı Karadeniz’den Doğu Karadeniz’e doğru uzanan bir kuşak üzerinde yaklaşık 4 dakika süre ile görülebilecektir. Bu çalışmada 29 mart 2006 tam güneş tutulmasının özelliği tutulma zamanları meteorolojik veriler halka ve turistlere yönelik hazırlıklar ve gözlem teknikleri gibi konular ele alınmıştır. Yurdumuz tekrar yakaladığı bu önemli fırsatı hem bilimsel hem de turizm açısından gereği gibi değerlendirebilmek için gerekli çalışmalar devam etmektedir.

The Solar eclipse is a magnificant natural event so that people can see maybe only once in their lifetimes if they do not move to another place. Our country will witness again a total solar eclipse on 29 March 2006 after the 11 August 1999 eclipse. This eclipse will be visible within a zone starting from western Mediterranean to eastern Black Sea regions during almost 4 minutes. On the other hand, TUBITAK National Observatory of Turkey lies within the zone of this totality. This work include the specifications of 29 March 2006 total solar eclipse, contact times, meteorological data, public organizations and observational techniques. Preparations have already begun in Antalya and at the National Observatory to utilize this rare fascinating event.
Keywords: güneş tutulması; solar eclipse